Mixing chia seeds and sprouts at different developmental stages: A cost-effective way to improve antioxidant vitamin composition - Bermejo, Núria F.; Munné-Bosch, Sergi (Food chemistry, 2023)
•Highest contents of vitamins C and E are found in germinating and dry seeds, respectively.•Abscisic acid application increases vitamin E in chia sprouts, but levels are still much lower than in dry seeds.•Mixing chia developmental stages allows an optimal antioxidant vitamin intake.•Exploiting the characteristic composition of different developmental stages within the same species can improve nutritional value. Various approaches can be used to improve chemical food composition avoiding the low acceptance risks that imply the use of transgenic crops. Here, we evaluated the antioxidant vitamin composition of dry and germinating seeds and sprouts of chia and examined the potential of exploiting natural variation of developmental stages to improve vitamin contents in chia-derived foodstuffs. Results showed that dry seeds contained the highest contents of vitamin E, with values 8-fold higher compared to sprouts. Vitamin C contents strongly increased just after seed imbibition, so that germinating seeds contained 5- and 17.5-fold higher values than dry seeds and sprouts, respectively. Sprouts displayed the highest contents of carotenoids (including β-carotene [pro-vitamin A]). We conclude that mixing dry seeds, germinating seeds and sprouts (in a proportion of 1.5:2:1 w/w/w) may be a cost-effective way to obtain an optimal composition of antioxidant vitamins in foodstuffs such as salads.